Virgin envy : the cultural (in)significance of the hymen - Santos, Cristina, 1972-; Spahr, Adriana, 1951-; Allan, Jonathan A (Exquisite corpse (University of Regina Press), 2016)
"Virgin Envy sets out to reconceive the ways we relate to virginity as a cultural construct. Who is a virgin? How do we lose our virginities? What if we regret our "first time"? Contributors to Virgin Envy examine everything from the medieval romance to Bollywood films to True Blood and Twilight, to destabilize the many "certainties" about sexual purity. In particular, the hymen is called into question. How is virginity determined for those without a hymen? How do we account for the ways in which the "geography of the hymen" has changed over the course of history? And what about male and queer virginity? Issues of commodification, postcoloniality, and religious diversity are also addressed."--